The Role of TOX in the Development of Innate Lymphoid Cells. (18th October 2015) - Seehus, Corey R.; Kaye, Jonathan
Abstract : TOX, an evolutionarily conserved member of the HMG-box family of proteins, is essential for the development of various cells of both the innate and adaptive immune system. TOX is required for the development of CD4 + T lineage cells in the thymus, including natural killer T and T regulatory cells, as well as development of natural killer cells and fetal lymphoid tissue inducer cells, the latter required for lymph node organogenesis. Recently, we have identified a broader role for TOX in the innate immune system, demonstrating that this nuclear protein is required for generation of bone marrow progenitors that have potential to give rise to all innate lymphoid cells. Innate lymphoid cells, classified according to transcription factor expression and cytokine secretion profiles, derive from common lymphoid progenitors in the bone marrow and require Notch signals for their development. We discuss here the role of TOX in specifying CLP toward an innate lymphoid cell fate and hypothesize a possible role for TOX in regulating Notch gene targets during innate lymphoid cell development.